Gabon : Second Review of the Extended Arrangement under the Extended Fund Facility, Request for Waivers of Nonobservance of Performance Criteria and Waivers of Applicability, and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for Gabon. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This paper discusses Gabon's Second Review of the Extended Arrangement Under the Extended Fund Facility, Requests for Waivers of Nonobservance of Performance Criteria and Waivers of Applicability, and Financing Assurances Review. The short-term outlook for Gabon remains challenging. Although a growth rebound in 2018 is expected given good prospects for foreign direct investment and higher oil prices, low non-oil revenue collections and tight short-term liquidity conditions at the Treasury will require decisive implementation of the recently announced fiscal consolidation plan. Timely clearance of domestic arrears is needed to strengthen banks' balance sheets and increase credit to the private sector to support growth, while clearance of external arrears is crucial to maintain Gabon's creditworthiness and access to external financing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet